2018
DOI: 10.1038/s41437-018-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of copy number variation in the worldwide goat population

Abstract: Goats (Capra hircus) are an important farm animal species. Copy number variation (CNV) represents a major source of genomic structural variation. We investigated the diversity of CNV distribution in goats using CaprineSNP50 genotyping data generated by the ADAPTmap Project. We identified 6286 putative CNVs in 1023 samples from 50 goat breeds using PennCNV. These CNVs were merged into 978 CNV regions, spanning ~262 Mb of total length and corresponding to ~8.96% of the goat genome. We then divided the samples in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
59
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 52 publications
(56 reference statements)
20
59
3
1
Order By: Relevance
“…A large proportion of the global CNVR identi ed in this study (65.1 %) are within the CNVR reported by Liu et al [18]. The remaining 34.9 % may comprise false positive CNVR and CNVR that were missed by the PennCNV algorithm used in the other study, considering the limitation of CNV detection using SNP data, which include limited coverage for genome, low resolution, and di culty in detecting novel and rare mutations.…”
Section: Discussionsupporting
confidence: 60%
“…A large proportion of the global CNVR identi ed in this study (65.1 %) are within the CNVR reported by Liu et al [18]. The remaining 34.9 % may comprise false positive CNVR and CNVR that were missed by the PennCNV algorithm used in the other study, considering the limitation of CNV detection using SNP data, which include limited coverage for genome, low resolution, and di culty in detecting novel and rare mutations.…”
Section: Discussionsupporting
confidence: 60%
“…The results suggest that there are negligible differences in the sizes of CNV between populations. Some of the CNV displayed large differences between populations, suggestive of population-specific selective pressures.A large proportion of the global CNVR identified in this study (65.1%) are within the CNVR reported by Liu et al[17]. The remaining 34.9% may comprise false positive CNVR and CNVR that were missed by the PennCNV algorithm used in the other study, considering the limitation of CNV detection using SNP data, which include limited coverage for genome, low resolution, and difficulty in detecting novel and rare mutations.…”
supporting
confidence: 59%
“…[68], Cardoso et al [69] and Colli et al [70], and some of them were also used for detection of CNV using 50 K SNP chip data, as reported by Liu et al [17]. A list of the breeds, populations and samples sizes used in the analysis is given in Table 4 while a full list of individual samples can be found in Supplementary Table 7 (Additional file 1).…”
Section: Sample Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNVs do not only extensively exist in the human genome, but have also been detected in various animal genomes. CNV maps of livestock species such as cattle, goats, sheep and pigs have already been published, and studies have shown that these CNVs have some influence on the production performance of livestock [5][6][7][8]. Zhang et al found that a 1 kb sequence deletion in the GBP2 gene of cattle was significantly correlated with growth and development characteristics, indicating that this CNV could serve as a marker for the molecular breeding of cattle [9].…”
Section: Introductionmentioning
confidence: 99%